The crime-culture connection in a crime fact story: An applied approach - Reshmi Dutta-Flanders (Cogent Social Sciences)
This paper explores “crime” as cultural and not simply an individual act. The aim is to contextualize a transgression as an outcome of a social “phenomenon” that happens in real-time, is reported in the newspaper and TV documentaries, and is adopted for analysis as a “crime fact story”. Using a “discourse-based” frame analysis of the non-linear narrative characteristic of offender engagement discourse, I reorganize the narrator’s experience. Secondly, in the narrative act of the “double function” of a narrator as a character, I reveal an “unreliable” stance when the narrator, like the transgressor, is the victim of the interpretations the actors make of their surroundings in the 1st story of crime. In reorganizing the narrator’s experience, there are “microcontexts” which, as alternative storyworld, emulate the causes leading to the transgression left unnarrated in the 2nd “story of investigation”. Consequently, a “perpetrator-culture” nexus is conceptualized in the dichotomy of social factors and criminal behaviour, which is a phenomenon and represented as antecedentless pronouns and inanimate nouns in the text, stylistically “repeated” for emphasis in the discourse. The paper emphasizes the need to consider the impact of factors that influence society and inform deviance within a context of “culture” that is of shared value and behaviour and situates an offence to the interpretations the actors cognitively make of their surroundings.